Teaching Social Sciences through Ethnophotography - Suciptaningsih, Oktaviani Adhi; Haryati, Titik (KOMUNITAS: International Journal of Indonesian Society and Culture, 2015)
Curriculum 2013 requires teachers to be more creative in compiling teaching materials which are innovative, varied, exciting, contextual, and in accordance with learners’ needs to achieve learning objectives. This research aims at developing IPS materials for VII graders of Junior High School (SMP) based on ethnophotography. This study used Research and Development design (R & D). The results were analyzed by qualitative analysis technique. The results show that most social studies (IPS) teachers have not yet developed the IPS materials for VII graders of SMP which is relevant to the environmental conditions. The ethnophotography was used to determine the development of IPS materials by photographing/taking pictures of each regional potential to be used as supporting material in IPS materials. Through ethnophotography, the students would be more interested and easier to learn the material, and at the same time, they learn a variety of region’s potential. In conclusion, the IPS material based on ethnophotography can be used as one of the ways to develop teaching materials to get more effective and efficient learning because students can easily understand the material through the photographs displayed in the teaching materials because the photographs show a variety of things around it.